Analysis of a Rigid Frame: Modified Corner Stiffness - Pitarresi, James (McGraw-Hill's AccessEngineering., 2012)
This video illustrates an example in Roarks' Formulas for Stress and Strain on rigid frames. A rigid frame is analyzed, accounting for minor deformation in the corner joint. Table 8.2 is used.